Lexical-semantic study of Arabic loanwords - Iskandarova , Sharifaxon; Amonov , Muxtorjon; Axmadaliyeva, Odina; Zikiryayeva , Xurshidaxon (The Lingua Spectrum, 2025)
This article discusses loanwords, mainly Arabic loanwords. Opinions are expressed about the semantics of Arabic loanwords and their semantic changes. Some Arabic lexemes found in the works of Ibrat, a representative of Jadid literature, are analyzed from a semantic and lexical perspective.